2020
DOI: 10.1109/access.2020.3041847
|View full text |Cite
|
Sign up to set email alerts
|

F-2D-QPCA: A Quaternion Principal Component Analysis Method for Color Face Recognition

Abstract: Two-dimensional quaternion principal component analysis (2D-QPCA) is one of the successful dimensionality reduction methods for color face recognition. However, 2D-QPCA is sensitive to outliers. For solving this shortcoming, an efficient robust method(F-2D-QPCA) is presented by means of Frobenius norm(F-norm). The goal of F-2D-QPCA is to find the projection matrix such that the projected data has the maximum variance based on F-norm, and it is more robust to outliers and has higher recognition accuracy than ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Due to the competitive performance of quaternion-based PCA and the theoretical guarantee, there are many related works [75]. For example, Wang et al [76] proposed a robust subspace learning method with PCA for face recognition under the Georgia Tech face dataset (https://computervisiononline.com/dataset/1105138700, accessed on 1 March 2023) and the color FERET (https://www.nist.gov/itl/iad/imagegroup/color-feret-database, accessed on 1 March 2023) dataset. Sun et al [77] suggested modified two-dimensional principal component analysis (2DPCA) and bidirectional principal component analysis (BDPCA) methods based on the quaternion matrix to recognize and reconstruct face images.…”
Section: Low-rank-based and Sparse-based Modelsmentioning
confidence: 99%
“…Due to the competitive performance of quaternion-based PCA and the theoretical guarantee, there are many related works [75]. For example, Wang et al [76] proposed a robust subspace learning method with PCA for face recognition under the Georgia Tech face dataset (https://computervisiononline.com/dataset/1105138700, accessed on 1 March 2023) and the color FERET (https://www.nist.gov/itl/iad/imagegroup/color-feret-database, accessed on 1 March 2023) dataset. Sun et al [77] suggested modified two-dimensional principal component analysis (2DPCA) and bidirectional principal component analysis (BDPCA) methods based on the quaternion matrix to recognize and reconstruct face images.…”
Section: Low-rank-based and Sparse-based Modelsmentioning
confidence: 99%
“…Xiao and Zhou [48] proposed a novel quaternion ridge regression model for 2D-QPCA and proposed the QRR-2D-QPCA. Wang et al [49] replaced square F-norm with F-norm in 2D-QPCA and proposed the F-2D-QPCA. Jia et al [50] replaced 2 -norm with p -norm in 2D-QPCA and proposed the generalized 2D-QPCA (G-2D-QPCA).…”
Section: Related Workmentioning
confidence: 99%
“…Bilateral algorithms Zhang et al [21] (2D) 2 PCA Kong et al [22] Generalized 2DPCA Yang et al [23] RC2DPCA Subimages Titijaroonroj et al [24] RCM-2DPCA Sahoo et al [25] ESIMPCA, EFLPCA Sahoo et al [26] Bi-ESIMPCA, Bi-EFLPCA Robust and sparse modelling Li et al [27] 2DPCA-L1 Wang et al [28] non-greedy 2DPCA-L1 Yang et al [29] 2DPCA-T 1 Wang and Wang [30] 2DPCAL1-S Wang [31] G2DPCA Rotational invariance Gao et al [34] R 1 -2DPCA Li et al [35] F-2DPCA Gao et al [36] Angle-2DPCA Wang and Li [37] Area-2DPCA Wang et al [38] Cos-2DPCA Bi et al [39] ROMCA-2DPCA Razzak et al [40] ORPCA Mi et al [41] 2,p -2DPCA Zhou et al [42] GC-2DPCA Kuang et al [43] F p -2DPCA Zhou et al [44] BA2DPCA Bi et al [45] 2,p -SB-2DPCA Color image processing Xiang et al [46] C-2DPCA Jia et al [47] 2D-QPCA Xiao and Zhou [48] QRR-2D-QPCA Wang et al [49] F-2D-QPCA Jia et al [50] G-2D-QPCA Zhao et al [ 2DPCA-Net Li et al [57] L1-2DPCA-Net…”
Section: Category Bibliography Algorithmmentioning
confidence: 99%
“…PCA has been found used in a wide range of fields ranging from spike-triggered covariance analysis in neuroscience [49], [50], to quantitative finance [51]- [54] with the most common application being facial recognition [54]- [56] and other applications like medical data correlation [57]- [60].…”
Section: Principal Component Analysismentioning
confidence: 99%